2016
DOI: 10.5944/rppc.vol.21.num.2.2016.16991
|View full text |Cite
|
Sign up to set email alerts
|

Diferencias y similitudes en la insatisfacción corporal entre personas con trastornos alimentarios, personas con disforia de género y estudiantes universitarios

Abstract: Abstract:To subjects with gender dysphoria, body image is an important aspect of their condition. These individuals at times report high body dissatisfaction, similar to individuals with an eating disorder. In total, 61 subjects with gender dysphoria, 30 subjects with an eating disorder, and 40 healthy subjects were evaluated. We parted from the hypothesis that gender dysphoria subjects present more body dissatisfaction than the control group, but less than the eating disorder group. Results regarding body dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 14 publications
0
4
0
3
Order By: Relevance
“…La imagen corporal se trata de un concepto multidimensional estudiado a lo largo de la historia y, cuya conceptualización, ha evolucionado desde principios del siglo XX especialmente (Baile, 2003; Rabito-Alcón & Rodríguez-Molina, 2015, 2016).…”
Section: Diferencias De Género Existentes En La Población General En ...unclassified
See 1 more Smart Citation
“…La imagen corporal se trata de un concepto multidimensional estudiado a lo largo de la historia y, cuya conceptualización, ha evolucionado desde principios del siglo XX especialmente (Baile, 2003; Rabito-Alcón & Rodríguez-Molina, 2015, 2016).…”
Section: Diferencias De Género Existentes En La Población General En ...unclassified
“…Body image is a multidimensional concept that has been studied throughout history and whose conceptualization has always been evolving, especially since the beginning of the twentieth century (Baile, 2003; Rabito-Alcón & Rodríguez-Molina, 2015, 2016).…”
mentioning
confidence: 99%
“…Así pues, emociones y comportamientos tan dispares como el miedo a ganar peso, el impulso a hacer dieta y/o ejercicio físico, o la necesidad de comprobar o verificar el peso, los impulsos de atracarse, o los de purgarse, tienen un carácter intruso y comportan rituales que interfieren y perjudican gravemente la calidad de vida de las personas. Además, a diferencia de lo que sucede con las IM-obsesivas, el estudio de los contenidos de IM que se producen en los TA brinda la oportunidad de trabajar con «contenidos» que son normativos y socialmente deseables y aceptados (Rabito-Alcón y Rodríguez-Molina, 2016).…”
Section: Intrusiones Mentales Relacionadas Con La Salud Y La Enfermedadunclassified
“…The results of research and phenomena can be said that individuals who have gender dysphoria is not easy (Dyla et al, 2020). Rabito-Alcón and Rodríguez-Molina (2016) showed that the dysphoria gender group had a lower value on self-satisfaction with the scale of life and psychological well-being than the control group. Matud et al, (2019) stated that most who can accept themselves as a change in gender characteristics experienced are men, while some women are still struggling with the impact of their social problems and low self-acceptance.…”
Section: Introductionmentioning
confidence: 91%